2011
DOI: 10.1016/j.jprot.2011.03.032
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometry imaging for drugs and metabolites

Abstract: Mass spectrometric imaging (MSI) is a powerful analytical technique that provides two- and three-dimensional spatial maps of multiple compounds in a single experiment. This technique has been routinely applied to protein, peptide, and lipid molecules with much less research reporting small molecule distributions, especially pharmaceutical drugs. This review’s main focus is to provide readers with an up-to-date description of the substrates and compounds that have been analyzed for drug and metabolite compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
97
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(98 citation statements)
references
References 73 publications
(108 reference statements)
0
97
0
1
Order By: Relevance
“…[8][9][10] Disease studies such as the fundamental understanding of the biochemistry of neurodegenerative diseases 11,12 or cancer, 13 drug distribution studies 10,14 and forensics, 15,16 among others, also benefit from the information revealed by MSI.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Disease studies such as the fundamental understanding of the biochemistry of neurodegenerative diseases 11,12 or cancer, 13 drug distribution studies 10,14 and forensics, 15,16 among others, also benefit from the information revealed by MSI.…”
Section: Introductionmentioning
confidence: 99%
“…MALDI-MSI (31) has been applied in the study of animal and human tissues as a research tool as well as in a medical diagnostic capacity in the study of disease pathology (32)(33)(34) and to monitor drug pharmacokinetics (35,36). Recent examples of plant MALDI-MSI providing insights through spatial information include the peptide analytes of developing soybean cotyledons (37), secreted peptide hormones involved in plant development in Arabidopsis roots (38), and small-molecule glucosinolate derivatives involved in plant defense from Arabidopsis leaves (39).…”
mentioning
confidence: 99%
“…Recent advancements in the field of IMS have specifically been reviewed and discussed showing the great potential of this technique in small molecule analysis [61,62]. Through a computer-controlled xy stage to the ionization source, the surface of the sample is typically scanned with a local desorbing and ionizing probe, and the generated ions from the surface are analyzed by MS [63].…”
Section: Imaging Msmentioning
confidence: 99%
“…In addition of MALDI, matrix-free LDI techniques have been proved to be useful in IMS studies of small molecules [62]. Thus, NIMS has also been proved to be a highly sensitive matrix-free method (in which functionalized surfaces are used to absorb the laser, eliminating the need for matrices) for tissue imaging in metabolomics [75,76].…”
Section: Imaging Msmentioning
confidence: 99%